2021
DOI: 10.1134/s0003683821020174
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactive Proteins of Dormant Mycobacterium tuberculosis Cells

Abstract: The protein profile of dormant Mtb obtained after the gradual acidification of Mtb culture was studied to find antigenic proteins for humans that are expressed by M. tuberculosis (Mtb) cells in vitro under conditions close to the situation of persistence in vivo. According to 2D electrophoresis, a significant diversity of proteins in dormant cells was found. However, the representation of individual proteins in dormant versus active cells differed substantially. Immunoblotting in different protein fractions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Among 62 seropositive TB proteins reported by Zhou et al, 12 proteins out of 40 were found in the current study. Additionally, experiments recently carried out on the sera of 42 TB patients allowed the detection of a set of 27 potentially immunoreactive proteins [ 85 ], six of them ( Rv2623 , Rv2018 , Rv2145c , Rv2744c , Rv1837c , Rv0341 ) similarly detected in the current study with a positive FC in the dormant state. It is to be anticipated that the list of selected antigenic proteins includes those that may be of interest for identifying the specific ‘immunosignature’ of latent TB, which can later be used for immunodiagnosis of latent TB.…”
Section: Discussionmentioning
confidence: 69%
“…Among 62 seropositive TB proteins reported by Zhou et al, 12 proteins out of 40 were found in the current study. Additionally, experiments recently carried out on the sera of 42 TB patients allowed the detection of a set of 27 potentially immunoreactive proteins [ 85 ], six of them ( Rv2623 , Rv2018 , Rv2145c , Rv2744c , Rv1837c , Rv0341 ) similarly detected in the current study with a positive FC in the dormant state. It is to be anticipated that the list of selected antigenic proteins includes those that may be of interest for identifying the specific ‘immunosignature’ of latent TB, which can later be used for immunodiagnosis of latent TB.…”
Section: Discussionmentioning
confidence: 69%
“…Among 62 seropositive TB proteins reported by Zhou et al, 12 proteins out of 40 were found in the current study. Additionally, experiments recently carried out on the sera of 42 TB patients allowed the detection of a set of 27 potentially immunoreactive proteins (74), six of them (Rv2623, Rv2018, Rv2145c, Rv2744c, Rv1837c, Rv0341) similarly detected in the curent study with a positive FC in the dormant state. It is to be anticipated that the list of selected antigenic proteins includes those that may be of interest for identifying the specific 'immunosignature' of latent TB, which can later be used for immunodiagnosis of latent TB.…”
Section: The High-throughput Lc-ms-based Reconstruction Of Central Carbon Metabolism Significantlymentioning
confidence: 99%